Power generation unit

The power generator with controlled pore diameter in the base material enhances power generation efficiency by optimizing liquid flow and contact area, addressing inefficiencies in existing methods.

JP7606355B2Active Publication Date: 2024-12-25NISSAN MOTOR CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021011616
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-28
Publication Date
2024-12-25
Estimated Expiration
2041-01-28

AI Technical Summary

Technical Problem

Existing power generation methods using liquid kinetic energy are inefficient due to limited contact area between the liquid and the power generation surface, leading to reduced power output.

Method used

A power generator with a base material having communication holes with an average diameter of 0.05 mm to 7 mm, covered by a conductive layer, and electrodes spaced apart to facilitate the flow of ion-containing liquid, utilizing contact charging and electrostatic induction to generate electricity.

Benefits of technology

The specified pore diameter range allows efficient flow of the ion-containing liquid, increasing the contact area and improving power generation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606355000005
    Figure 0007606355000005
  • Figure 0007606355000001
    Figure 0007606355000001
  • Figure 0007606355000002
    Figure 0007606355000002
Patent Text Reader

Abstract

To provide a power generating body having a large specific surface area of the power generating surface in one power generating body and capable of improving the amount of power generated.SOLUTION: A power generating body comprises a substrate having communication holes communicating from one surface to the opposite surface, a conductive layer covering at least the inner surface of the communication holes, an ion-containing liquid flowing through the communication holes, and two electrodes spaced apart in the flow direction of the ion-containing liquid and having contact with the conductive layer. The power generating body generates power by moving the electric charges of the conductive layer attracted by the electric charges of the ion-containing liquid due to the flow of the ion-containing liquid and extracting the electric charges to the outside through the electrodes. The average pore diameter of the communication holes is more than 0.05 mm and less than 7 mm, which allows the ion-containing liquid to flow quickly through the communication holes to improve the amount of power generated.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a power generator, and more particularly to a power generator that utilizes contact electrification and electrostatic induction. [Background technology]

[0002] Electricity is generated by utilizing contact electrification and electrostatic induction between materials with different electron affinities.

[0003] Contact electrification is a phenomenon in which when two objects with different work functions are brought into contact, one object gains an electric charge and becomes negatively charged, while the other object loses electric charge and becomes positively charged.

[0004] Electrostatic induction is a phenomenon in which, when a charged object is brought close to a conductor, a charge of the opposite polarity to that of the charged object is attracted to the side closer to the charged object, and is caused by the actual movement of charge through the conductor.

[0005] If there is no conductive path between the surfaces of these charged objects, they will maintain an induced charge on their surfaces, and when the two objects are moved relative to each other while maintaining this induced charge, a potential difference is created, and the charge can be transported, generating electricity.

[0006] Patent Document 1 describes a frictional electric nanogenerator that generates electricity by utilizing the kinetic energy of liquids such as waves, and discloses that by covering the two electrodes with an insulator, the electrodes do not come into contact with the liquid in the power generation environment, allowing for stable operation for long periods of time. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2016-529868 Summary of the Invention [Problem to be solved by the invention]

[0008] In the above-mentioned power generation method, in order to efficiently utilize the kinetic energy of the liquid to increase the amount of generated electricity, it is effective to increase the amount of contact between the liquid per unit volume and the power generation surface, and it is preferable for the liquid to spread thinly over the power generation surface and move.

[0009] However, if the power generation surface has a planar shape, the liquid on the power generation surface is in contact with the power generation surface only on one side thereof, making it difficult to increase the amount of generated power.

[0010] If the shape of the power generation surface is a shape that surrounds the liquid, such as a communicating hole, the entire periphery of the liquid droplets will come into contact with the power generation surface, increasing the amount of liquid per unit volume that comes into contact with the power generation surface, thereby improving the amount of power generated.

[0011] However, if the diameter of the communicating hole is made too small in order to increase the amount of contact between the liquid and the power generation surface per unit volume, i.e., if the liquid flow is made too thin, the liquid flow will be stagnated inside the communicating hole and power generation will not be possible.

[0012] The present invention has been made in consideration of the problems associated with the conventional technology, and its object is to provide a power generator that can efficiently utilize the kinetic energy of liquid and increase the amount of generated electricity. [Means for solving the problem]

[0013] As a result of extensive research into achieving the above-mentioned objective, the inventors discovered that by setting the average pore size of the communicating holes within the desired range, the ion-containing liquid can flow down the communicating holes quickly, thereby achieving the above-mentioned objective, and thus completed the present invention.

[0014] That is, the power generating unit of the present invention is A substrate having a through hole extending from one surface to the other surface facing the substrate, a conductive layer covering at least the inner surface of the through hole, and a conductive layer covering the inside of the through hole. Flows from one surface down to the opposite surfaceAn ion-containing liquid and two electrodes arranged at a distance from each other in a flow direction of the ion-containing liquid and having contacts with the conductive layer, The flow of the ion-containing liquid causes the charges in the conductive layer to be attracted to the charges in the ion-containing liquid, which then moves and is taken out to the outside via the electrode, thereby generating electricity. The communicating holes have an average diameter of more than 0.05 mm and less than 7 mm. Effect of the Invention

[0015] According to the present invention, the average pore size of the communicating holes is set within a desired range, thereby enabling the ion-containing liquid to flow quickly through the communicating holes, thereby providing a power generating body that can improve the amount of generated electricity. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a diagram illustrating a power generation mechanism that utilizes contact charging and electrostatic induction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The power generating unit of the present invention will now be described in detail. The power generator comprises a conductive layer covering the surface of a substrate, and two electrodes spaced apart in the in-plane direction of the conductive layer and having contact with the conductive layer, and generates power by causing an ion-containing liquid to flow over the surface of the conductive layer.

[0018] Although the principle of power generation by the above power generating body has not been completely clarified, it is thought to be as follows.

[0019] As shown in FIG. 1, when the base material and the conductive layer are in contact with each other, the one with the larger work function is positively charged and the one with the smaller work function is negatively charged due to contact electrification.

[0020] Since the substrate is electrically charged, an imbalance in the charges occurs between the substrate side and the surface side of the conductive layer in contact with the substrate due to electrostatic induction, and charges opposite to the charges on the surface side of the conductive layer also gather on the conductive layer side of the ion-containing liquid due to electrostatic induction, and these charges attract each other.

[0021] Therefore, when the ion-containing liquid flows over the conductive layer in a direction that crosses both of the two electrodes, the charges in the conductive layer are attracted to the charges in the ion-containing liquid and move, and by extracting this to the outside, electricity can be generated.

[0022] In the power generating unit of the present invention, the average pore diameter of the communicating pores formed in the substrate is greater than 0.05 mm and less than 7 mm, so that the ion-containing liquid flows quickly down through the communicating pores, thereby improving the amount of generated electricity.

[0023] If the average pore size of the communicating holes is 0.05 mm or less, the ion-containing liquid will not enter the communicating holes, or the surface tension (capillary phenomenon) of the ion-containing liquid against the gravitational acceleration will become so large that the ion-containing liquid will remain in the communicating holes and will be difficult to flow downward, resulting in a decrease in the amount of generated power.

[0024] Furthermore, if the average pore diameter of the communicating holes is 7 mm or more, the flow of ion-containing liquid flowing down through the communicating holes becomes thicker and the amount of contact with the conductive layer (power generation surface) becomes smaller, making it difficult to increase the amount of generated electricity.

[0025] Furthermore, when the average pore diameter of the communicating holes is 1 mm to 3 mm, the thickness of the flow of the ion-containing liquid flowing down through the communicating holes, i.e., the increased contact area between the conductive layer and the ion-containing liquid, is well balanced with the flow rate of the ion-containing liquid, thereby increasing the amount of generated power.

[0026] The average opening diameter of the communicating pores can be calculated by photographing the surface of the substrate with a CCD camera and binarizing the resulting image.

[0027] (base material) The substrate may have communicating holes through which the ion-containing liquid flows, but preferably has a porous structure formed by a group of a plurality of such communicating holes. When a porous structure is formed by the above-mentioned communicating holes, the specific surface area of ​​the conductive layer (power generation surface) in one power generating element increases, improving the amount of generated power.

[0028] The substrate may be one consisting of only a porous structure portion, or may have a structure in which the porous structure portion is supported by a support portion.

[0029] The substrate may be made of any material that has lower electrical conductivity than the conductive layer and a different work function from that of the conductive layer, but is preferably made of an insulator.

[0030] When the conductivity of the porous structure portion increases, the porous structure portion supplies the conductive layer with charges opposite to the charge of the conductive layer, making it easier for the charge of the conductive layer to be cancelled out. As a result, even if the ion-containing liquid flows, the charges in the conductive layer are less likely to move, making it difficult to increase the amount of generated power.

[0031] As the insulator, metal oxides such as aluminum oxide, silicon oxide, zinc oxide, and titanium oxide, as well as resins such as polyester resin, urethane resin, acrylic resin, and polystyrene can be used. The material constituting the support portion may be the same as or different from the material of the porous structure portion.

[0032] The structure of the porous structure portion may be a so-called sponge-like porous structure in which voids are arranged randomly in three dimensions and multiple voids are connected to form communicating holes, a structure in which multiple linear communicating holes are arranged in one direction like multiple tubes arranged in parallel, or a structure that combines these structures.

[0033] The porous structure of metal oxides can be formed by adding a pore-forming material such as resin particles to the raw material and firing it when producing ceramics using the sol-gel method. The porous structure of resins can be formed by adding a pore-forming agent such as a phase separation agent or a foaming agent to the monomer component and polymerizing and curing it. It can also be formed by drilling multiple interconnecting holes in a mass of metal oxide or resin.

[0034] (Conductive layer) The conductive layer may be made of a conductor that allows electric charges to move within the conductive layer by electrostatic induction. By increasing the conductivity of the conductive layer, the internal resistance of the power generator is reduced and the amount of generated power is improved, so the main component of the conductive layer is preferably a metal or conductive carbon. In the present invention, the term "main component" refers to 50% by mass or more.

[0035] Examples of the metals include metals with high electrical conductivity such as platinum (Pt), gold (Au), silver (Ag), copper (Cu), aluminum (Al), zinc (Zn), nickel (Ni), manganese (Mn), chromium (Cr), iron (Fe), cobalt (Co), and molybdenum (Mo), as well as alloys containing these metals.

[0036] When an oxide layer is formed on the outermost surface of the conductive layer made of the above metal, charge is less likely to be transferred between the conductive layer and the ion-containing liquid, and charge is more likely to be generated on the surface. In this context, the oxide layer refers to a layer formed by the oxidation of the metal itself, such as an oxide layer formed naturally on the surface of a metal when the metal is exposed to air at room temperature, or an oxide layer formed by oxidizing a metal through heat treatment, etc., and does not refer to an oxide layer formed by stacking oxides of other materials.

[0037] Examples of the conductive carbon include graphene, carbon nanotubes, carbon nanofibers, carbon black, and graphite. Among these, graphene, carbon nanotubes, and carbon nanofibers are preferably used because of their high electrical conductivity.

[0038] The surface of the conductive layer, i.e., the inner surface of the communicating hole, preferably has projections and recesses. By providing projections and recesses, the surface area of ​​the conductive layer increases, improving the amount of generated power.

[0039] Furthermore, when the through holes are linear, such as cylindrical, friction between the ion-containing liquid and the inner wall of the through hole causes a difference in flow rate between the inner wall and the center of the through hole, generating a vortex. The reverse flow caused by this vortex cancels the movement of charges inside the ion-containing liquid, making it difficult to move charges in the conductive layer.

[0040] The unevenness of the surface of the conductive layer prevents the generation of eddy currents and makes the flow of the ion-containing liquid laminar, enabling power generation at a high voltage. The hole diameter of the recesses that prevent the generation of vortex currents is preferably 1 to 100 μm, although it depends on the viscosity of the ion-containing liquid and other factors.

[0041] The unevenness of the conductive layer surface may be formed in the conductive layer itself, or the shape of the inner surface of the communicating holes of the substrate may be reflected on the conductive layer surface.

[0042] The conductive layer may include a wettability adjuster. As the wettability adjusting agent, a surfactant or a water repellent agent can be used. The surfactant allows the ion-containing liquid to easily enter the communicating holes, and the water repellent agent allows the ion-containing liquid that has entered the communicating holes to flow quickly downward, making it possible to generate power at a high voltage.

[0043] As the surfactant, a nonionic surfactant such as polyoxyethylene alkyl ether or polyoxyethylene polyoxypropylene glycol can be used. The nonionic surfactant does not affect the charge in the ionic liquid because the hydrophilic group such as the hydroxyl group (OH) does not dissociate in water. The amount of the wettability adjuster added is preferably 0.1 to 1 mass %.

[0044] Examples of the water repellent include silicone-based materials and fluorine-based materials. For example, powders of silicone rubber or silicone resin, fluorine-based resin powders and dispersions of these powders, resin paints, silicone oils, fluorine oils, and the like can be used.

[0045] The thickness of the conductive layer depends on the material composition of the conductive layer, but is preferably 10 nm to 1 μm.

[0046] The conductive layer can be formed by applying a coating liquid containing a metal or conductive carbon and drying it, or by plating, sputtering, or the like.

[0047] (Ion-containing liquid) The ion-containing liquid is required to flow down through the communicating holes while carrying the charges in the conductive layer with it. A solution containing salt as a solute or an ionic liquid (room temperature molten salt) can be used. However, since ionic liquids generally have a high viscosity, a solution containing dissolved salt is preferable.

[0048] Examples of the solvent for the solution include water and organic solvents. Water is a good solvent for salts and is preferred because it makes it easy to increase the ion concentration in the ion-containing liquid.

[0049] Examples of the salt to be dissolved in the solution include inorganic salts such as lithium salts, potassium salts, sodium salts, and magnesium salts, as well as organic salts.

[0050] Among these, it is preferable that the main component of the cation is at least one selected from the group consisting of lithium ions, sodium ions, and magnesium ions.

[0051] Salts of these cations have high solubility in water, making it possible to increase the ion concentration in the ion-containing liquid. In addition, aqueous solutions mainly composed of these cations have a viscosity of 0.8-1 mPa s at room temperature and low surface tension, so they flow quickly without remaining in the pores, enabling high-voltage power generation. EXAMPLES

[0052] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.

[0053] [Comparative Example 1] Graphene powder (manufactured by The Sixth Element Co., Ltd.) was dispersed in pure water containing 0.5 mass% polyoxyethylene alkyl ether (manufactured by Kao Corporation: Emulgen 709), and carbon nanotubes and a styrene-butadiene rubber dispersion were further added and dispersed to obtain a coating liquid with a solid content ratio of graphene powder:carbon nanotubes:styrene-butadiene rubber of 20:40:20.

[0054] A sponge-like alumina porous body (average opening diameter: 0.05 mm) having outer dimensions of 1 cm×1 cm×5 cm was dip-coated with the above coating liquid and dried at 120° C. to form a conductive layer. Platinum wire was wound around both ends of this alumina porous body to form electrodes, thereby obtaining a power generator.

[0055] [Example 1] A power generating unit was obtained in the same manner as in Comparative Example 1, except that an alumina porous body having an average opening diameter of 0.1 mm (AZPW40 manufactured by Asuzak Co., Ltd.) was used.

[0056] [Example 2] A power generating unit was obtained in the same manner as in Comparative Example 1, except that an alumina porous body having an average opening diameter of 0.5 mm (AZPW45 manufactured by Asuzak Co., Ltd.) was used.

[0057] [Example 3] A power generating unit was obtained in the same manner as in Comparative Example 1, except that an alumina porous body (AZP60 manufactured by Asuzac Co., Ltd.) with an average opening diameter of 0.05 mm was cut with a drill with a diameter of 1.0 mm to form five through holes.

[0058] [Example 4] A power generating unit was obtained in the same manner as in Comparative Example 1, except that an alumina porous body having an average opening diameter of 0.05 mm was cut with a drill having a diameter of 3.0 mm to form four through holes.

[0059] [Example 5] A power generating unit was obtained in the same manner as in Comparative Example 1, except that an alumina porous body having an average opening diameter of 0.05 mm was cut with a drill having a diameter of 5.0 mm to form one through hole.

[0060] [Comparative Example 2] A power generating unit was obtained in the same manner as in Comparative Example 1, except that an alumina porous body having an average opening diameter of 0.05 mm was cut with a drill having a diameter of 7.0 mm to form one through hole.

[0061] [Example 6] A single layer of graphene was coated onto a polyethylene terephthalate (PET) film using the CVD method to form a conductive layer. The PET film was rolled into a tube with a diameter of 3 mm and a length of 5 cm, and platinum wires were drawn from the conductive layer on both ends of the tube to obtain a generator.

[0062] <Evaluation> A resistor of 100 Ω was connected between the electrodes of the above power generator, and the power generator was placed in a 1 cm square columnar tube so as to prevent the ion-containing liquid from leaking out from the side of the alumina porous body. 50 ml of a 4 mol / l aqueous potassium chloride solution was poured into the top of the upright column and allowed to flow down the generator with a drop of 5 cm, and the potential difference generated between the electrodes was measured. The measurement results are shown in Table 1 together with the shape of the porous structure.

[0063] [Table 1]

[0064] In Examples 1 to 5 in which the substrate had a porous structure, and in Example 6 in which the substrate was a circular tube, the average pore diameter of the communicating holes was greater than 0.05 mm and less than 7 mm, so that the potassium chloride aqueous solution flowed downward, enabling efficient power generation.

[0065] In Comparative Example 1, power generation was possible at first, but because the average pore size of the communicating holes was 0.05 mm, when the amount of the potassium chloride aqueous solution in the columnar vessel decreased, the potassium chloride aqueous solution did not flow downward and remained inside the generator.

[0066] In Comparative Example 2, since the average pore diameter of the communicating pores was 7 mm, electricity could be generated at a high voltage, but the surface area of ​​the conductive layer was small, resulting in a reduced amount of generated electricity.

[0067] Moreover, a comparison between Example 4 and Example 6 confirmed that the power generating element having a porous structure portion has an increased surface area of ​​the conductive layer, thereby further improving the amount of generated power.

[0068] Although the surface area of ​​the conductive layer in Example 6 is smaller than that in Example 5, the amount of generated power is greater. This is probably because the conductive layer of graphene formed by CVD has a uniform graphene layer and has higher conductivity and lower internal resistance than a conductive layer in which graphene powder is bound with a binder.

[0069] [Example 7] The potential difference was measured in the same manner as in Example 4, except that the potassium chloride aqueous solution was changed to a 4 mol / l sodium chloride aqueous solution.

[0070] [Example 8] The potential difference was measured in the same manner as in Example 4, except that the potassium chloride aqueous solution was changed to a 4 mol / l lithium chloride aqueous solution.

[0071] [Example 9] The potential difference was measured in the same manner as in Example 4, except that the potassium chloride aqueous solution was changed to a 4 mol / l magnesium chloride aqueous solution.

[0072] [Example 10] The potential difference was measured in the same manner as in Example 4, except that the potassium chloride aqueous solution was replaced with a propylene carbonate (PC) solution containing 4 mol / l of (C2H5)4NBF4 (TEABF4).

[0073] [Table 2]

[0074] A comparison of Example 4 with Examples 7 and 8 shows that the amount of generated electric power increases with the element's location at the top of the periodic table. Also, a comparison of Example 7 with Example 9 shows that the amount of generated electric power increases with alkali metal ions more than with alkaline earth metal ions. Moreover, it is clear from Example 10 that electricity can be generated even with a non-aqueous ion-containing liquid.

[0075] [Example 11] A power generator was obtained in the same manner as in Example 2, except that a conductive layer having a thickness of 0.1 μm was formed by electroless Ni plating on an alumina porous body having an average opening diameter of 0.5 mm.

[0076] [Example 12] A power generating body was obtained in the same manner as in Example 2, except that a Pt-Pd film having a thickness of 10 nm was formed by sputtering on an alumina porous body having an average opening diameter of 0.5 mm.

[0077] [Example 13] A power generating unit was obtained in the same manner as in Example 2, except that the graphene in the coating liquid was replaced with flake graphite (SP20 manufactured by Nippon Graphite Co., Ltd.).

[0078] [Example 14] A power generating unit was obtained in the same manner as in Example 2, except that the graphene in the coating liquid was replaced with acetylene black (HS-1000, manufactured by Denka Co., Ltd.).

[0079] The power generating unit was evaluated. The evaluation results are shown in Table 3.

[0080] [Table 3]

[0081] A comparison between Example 11 and Example 12 shows that the amount of generated electricity increases as the electrical conductivity of the conductive layer increases. It is believed that the amount of generated electric power was lower in Example 13 than in Example 14 because the flake graphite in Example 13 has anisotropy in electrical conductivity depending on the crystal direction.

[0082] [Example 15] A conductive layer was formed using a coating liquid containing no polyoxyethylene alkyl ether, and then the layer was immersed in a water repellent dispersion (polytetrafluoroethylene polymer particle dispersion: Daikin Corporation: D-210C) to obtain a generator in the same manner as in Example 8.

[0083] [Example 16] After the conductive layer was formed, a power generating unit was obtained in the same manner as in Example 8, except that it was immersed in a water repellent dispersion liquid.

[0084] [Example 17] A power generating unit was obtained in the same manner as in Example 8, except that the conductive layer was formed using a coating liquid containing no polyoxyethylene alkyl ether.

[0085] The power generator was evaluated. The evaluation results are shown in Table 4.

[0086] [Table 4]

[0087] The results in Table 4 show that the surfactant facilitates the entry of the ion-containing liquid into the communicating pores, but once inside the communicating pores, it does not contribute to improving the amount of generated power. It is also understood that after the ion-containing liquid enters the communicating holes, the conductive layer is less likely to become wetted by the ion-containing liquid, which improves the amount of generated electric power. [Explanation of symbols]

[0088] 1 Power generation unit 2 Base material (porous structure part) 3 Conductive layer 4 electrodes 5. Ion-containing liquids

Claims

1. A substrate having a through hole extending from one surface to the other surface opposite thereto; a conductive layer covering at least the inner surface of the communication hole; an ion-containing liquid flowing down through the communication holes from one surface to the opposing other surface; two electrodes arranged apart in a flow direction of the ion-containing liquid and having contacts with the conductive layer; a power generating unit that generates electricity by the flow of the ion-containing liquid causing charges in the conductive layer to be attracted to the charges in the ion-containing liquid and to move and then extracting the charges to the outside via the electrode, A power generating body characterized in that the average pore diameter of the communicating holes is greater than 0.05 mm and less than 7 mm.

2. 2. The power generating unit according to claim 1, wherein the substrate has a porous structure in which a plurality of the communication holes are formed.

3. The power generator described in claim 2, characterized in that the porous structure portion has a structure in which voids are randomly arranged in three dimensions and a plurality of voids are connected to form communicating holes, and / or a structure in which a plurality of linear communicating holes are arranged in one direction.

4. 4. The power generating unit according to claim 1, wherein the inner surface of the communication hole has projections and recesses.

5. 5. The power generating unit according to claim 1, wherein the base material is made of an insulating material.

6. 6. The power generating unit according to claim 1, wherein the solvent of the ion-containing liquid is water.

7. 7. The power generating unit according to claim 6, wherein the ion-containing liquid has a main component of solute cations which is at least one type of ion selected from the group consisting of lithium ions, sodium ions, and magnesium ions.

8. 8. The power generating unit according to claim 1, wherein the conductive layer is mainly composed of a metal.

9. 8. The power generating unit according to claim 1, wherein the conductive layer is mainly composed of carbon.

10. The power generating unit according to claim 9 , wherein the conductive layer contains at least one selected from the group consisting of graphene, carbon nanotubes, and carbon nanofibers.

11. The power generating unit according to any one of claims 1 to 10, characterized in that the conductive layer contains a wettability adjusting material.

12. A power generator as described in claim 1, characterized in that the average hole diameter of the communicating holes is 1 mm to 3 mm.

Citation Information

Patent Citations

  • Fuel cell

    JP2005251715A

  • Frictional electric nanogenerator for collecting mechanical energy of liquid and power generation method

    JP2016529868A

  • hybrid electrochemical capacitor

    JP2017500736A

  • Electrode and manufacturing method thereof

    JP2020167041A

  • An electrical generator and method of generating an electrical current

    WO2021008940A1